1983
DOI: 10.1128/mcb.3.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S14 is altered by two-step emetine resistance mutations in Chinese hamster cells.

Abstract: Four two-dimensional polyacrylamide gel electrophoresis systems were used to identify 78 Chinese hamster cell ribosomal proteins by the uniform nomenclature based on rat liver ribosomal proteins. The 40S ribosomal subunit protein affected by Chinese hamster ovary (CHO) cell one-step emetine resistance mutations is designated S14 in the standard nomenclature. To seek unambiguous genetic evidence for a cause and effect relationship between CHO cell emetine resistance and mutations in the S14 gene, we mutagenized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
36
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…S14 cDNA probes detect multiple bands in restriction digests of Chinese hamster genomic DNA (34,35). However, because recessive emtB (S14) CHO cell clones are obtainable by single-step mutagenesis, it appears that they express only a single S14 gene (5,27,35). Others mapped the emtB locus to a region of chromosome 2 that is hemizygous in CHO cells (64,65).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…S14 cDNA probes detect multiple bands in restriction digests of Chinese hamster genomic DNA (34,35). However, because recessive emtB (S14) CHO cell clones are obtainable by single-step mutagenesis, it appears that they express only a single S14 gene (5,27,35). Others mapped the emtB locus to a region of chromosome 2 that is hemizygous in CHO cells (64,65).…”
mentioning
confidence: 99%
“…This gene is the target of emetine resistance mutations, as emtB Chinese hamster ovary (CHO) cell mutants elaborate altered S14 mRNAs and polypeptides (4,5,27,28,35,37,45). We have isolated Chinese hamster S14 and other r-protein cDNAs (35) and have demonstrated that emtB S14 alleles differ from wild type by single base changes in two adjacent arginine codons at the 3' ends of their coding sequences (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The human RPS14 locus encodes ribosomal protein S14 and is especially well suited for these studies. It is the only mammalian r-protein locus in which a drug selection system facilitates somatic genetics (Boersma et al 1979;Madjar et al 1982Madjar et al , 1983Diaz et al 1990;Diaz and Roufa 1992;Tasheva and Roufa 1993) and for which both genomic and eDNA clones carrying numerous wild-type and mutant alleles are available (Rhoads et al 1986;Rhoads and Roufa 1987;Diaz et al 1990;Overman et al 1993).…”
mentioning
confidence: 99%
“…Recessive mutations (EmtB) affecting the CHO cell r-protein S14 gene (RPS14) result in resistance to emetine, an alkaloid inhibitor of protein biosynthesis (2,3,16,17,24). EmtB S14 protein is slightly more acidic than wild-type S14 (2), and ribosomes containing mutant S14 are relatively unstable (23,45). RPS14 genomic and cDNA sequences have been cloned from Chinese hamster and human cells, and their complete nucleic acid sequences are known (32,37,38).…”
mentioning
confidence: 99%